Management information systems - Lewandowski, Jerzy (Wydawnictwo Politechniki Łódzkiej, 2008)
Management information systems for many years have been an area of interest of scientists, systems designers, organisers as well as institutions and economic entities. This interest results from the fact that neither contemporary nor future management can exist without appropriate information support. Such support should assure provision of data necessary for decision making. A question of information systems gains special meaning in enterprises in which systems of computer support are installed. In order to fulfil information needs declared by managers attention should be paid to the processes they realise and sources of information they use for decision making. The problems presented above require system solutions, in particular concentrating on the problem of designing management information systems. The book is a monograph elaborated to analyse and systematise scientific and research output in the area of designing management information systems in a complex approach. The book is divided into six chapters. The first one is an introduction to information systems in an enterprise. The second chapter broadens the range of problems of information systems. It provides information model of a problem, models of information solutions and information systems functioning. Chapter three gives insight into management information systems design. Approach to problems of information systems design is presented in a complex way. The significance of information systems integration with controlling systems is highlighted. An example of an information system structure is given. In the final part of the chapter the meaning of integrated information systems as the basis for functioning of a computer system of management support is highlighted. In chapter four methods and techniques of management information systems design are discussed, and analytical design methods, organisation charts, forms and documents design are presented. Chapter five is devoted to directions in development of information systems in economic organisations. The significance of information systems in knowledge-based economy is stressed. Problem areas of knowledge management and postulates of its implementation in an enterprise are presented. Tendencies in development of computer systems in enterprise are discussed in the final part of the chapter. Chapter six is an original achievement of the author. In this chapter application of ergonomics in management information systems design is presented in complex way for the first time. Presentation of remarks concerning practical use of rules of ergonomics in information systems design is particularly important. Introduction of problems of occupational safety and hygiene at workposts equipped with screen displays closes the chapter. The study has been developed for the scientists dealing with problems of management information systems. It will be also useful for information systems designers dealing with interface ergonomics. The knowledge provided by the monograph can be also used by students of technical and university studies.

Systemy informacyjne zarządzania są od wielu lat obszarem zainteresowania naukowców, projektantów systemów, organizatorów oraz instytucji i podmiotów gospodarczych. Wynika to z faktu, że współczesne, jak i przyszłe zarządzanie nie może istnieć bez odpowiedniego wspomagania informacyjnego. Wspomaganie to powinno zapewnić dostarczanie danych niezbędnych do podejmowania decyzji. Zagadnienie systemów informacyjnych nabiera szczególnego znaczenia w przedsiębiorstwach, w których zainstalowane są systemy komputerowego wspomagania. W celu zaspokojenia potrzeb informacyjnych zgłaszanych przez menadżerów należy zwrócić uwagę na realizowane przez nich procesy oraz na wykorzystywane przy podejmowaniu decyzji źródła informacji. Zaprezentowana powyżej problematyka wymaga rozwiązania systemowego, a w szczególności zwrócenie uwagi na zagadnienie projektowania systemów informacyjnych zarządzania. Książka jest opracowaniem monograficznym, którego celem jest analiza i systematyka dotychczasowego dorobku naukowo-badawczego dotyczącego projektowania systemów informacyjnych zarządzania w ujęciu kompleksowym. Książka składa się z sześciu rozdziałów. W pierwszym rozdziale dokonano wprowadzenia do systemów informacyjnych zarządzania. W sposób syntetyczny przedstawiono problematykę systemów informacyjnych w przedsiębiorstwie. Drugi rozdział zawiera rozszerzenie problematyki systemów informacyjnych. Zaprezentowano w nim informacyjny model problemu, modele rozwiązań informacyjnych oraz funkcjonowanie systemów informacyjnych. Kolejny rozdział, trzeci, zawiera projektowanie systemów informacyjnych zarządzania. W sposób kompleksowy zaprezentowano podejście do problematyki projektowania systemów informacyjnych. Podkreślono znaczenie integracji systemu informacyjnego z systemem controllingu. W zakończeniu rozdziału podkreślono znaczenie zintegrowanych systemów informacyjnych jako podstawy funkcjonowania systemu komputerowego wspomagania zarządzania. W czwartym rozdziale omówiono metody i techniki w projektowaniu systemów informacyjnych zarządzania. Zaprezentowano analityczne metody projektowania, wykresy organizacyjne, projektowanie druków i formularzy dokumentów. Rozdział piąty poświęcony został kierunkom rozwoju systemów informacyjnych w organizacjach gospodarczych. Podkreślono znaczenie systemów informacyjnych w gospodarce opartej na wiedzy. Zaprezentowano obszary problemowe zarządzania wiedzą oraz postulaty jej wdrażania w przedsiębiorstwie. W zakończeniu omówiono tendencje rozwojowe systemów komputerowych w przedsiębiorstwie. Rozdział szósty jest oryginalnym osiągnięciem autora. W rozdziale tym po raz pierwszy zaprezentowano w ujęciu kompleksowym, zastosowanie ergonomii w projektowaniu systemów informacyjnych zarządzania. Szczególnie istotne jest przedstawienie uwag dotyczących praktycznego wykorzystania zasad ergonomii w projektowaniu systemów informacyjnych. W zakończeniu rozdziału omówiono problematykę bezpieczeństwa i higieny pracy na stanowiskach pracy wyposażonych w monitory ekranowe. Opracowanie jest przeznaczone dla naukowców zajmujących się problematyką systemów informacyjnych zarządzania. Będzie ono również przydatne dla projektantów systemów informacyjnych zajmujących się ergonomicznością interfejsu. Wiedza zawarta w monografii może być także wykorzystana przez studentów uczelni technicznych i uniwersyteckich.
Keywords: systemy informacyjne - zarządzanie; system informacyjny; ergonomia; projektowanie systemów informacyjnych; information systems - management; information systems; ergonomics; information systems design